Multi-dimensional transient temperature simulation and back-calculation for thermal properties of building materials - Li, Hui; Harvey, John; Jones, David (Building and environment, 2013)
Thermal properties (i.e. thermal conductivity and heat capacity) are important parameters that influence the temperature of building materials and thermal performance of built environment. These properties are required as fundamental inputs for modeling and simulating thermal behavior of built environment. Most existing methods for measuring thermal properties of building materials are based on 1-D steady-state heat transfer theory. The critical challenge for these methods has been the difficulty in achieving a 1-D heat flow condition for the testing specimen. A multi-dimensional transient method is needed to reduce the challenge and requirement on the testing specimen size and shape, and make it possible to accurately measure all the thermal properties from one single test. This paper first developed a multi-dimensional transient model and a practical tool to simulate the transient temperature at any location on a beam or cylinder specimen of any size subject to convection heat transfer. Case studies verified that this model can be used to, if the thermal properties are known, simulate the transient temperature at any location for a specimen of various shapes and sizes, and predict the time to reach a specified target temperature for mechanical and other testing. Secondly, this paper developed and validated partly by case studies on both asphalt and concrete materials a procedure for back-calculating the thermal properties of a specimen of various shapes and sizes. Thermal properties of novel building materials (various initiative cool materials such as porous concrete and high thermal resistance materials) can be easily measured with that procedure. ► A multi-dimensional transient temperature model and a tool were developed. ► Transient temperature can be simulated using the model and tool developed. ► A procedure for back-calculating thermal properties was developed and validated. ► Thermal properties of building materials can be easily measured with the procedure.